MODEL PENINGKATAN PERILAKU HEALTH MAINTANANCE ANAK BERBASIS INDIVIDUAL COACHING PADA MASA PANDEMI COVID-19 - Pembronia Nona Fembi Fembi; Yosefina Nelista Yosefina (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
The COVID-19 pandemic is a challenge throughout the world, where children are one of the most vulnerable groups. Children are the assets of the nation and the future generations of the ideals of the nation's struggle that will determine the future of the nation and state. Therefore, great attention and hope needs to be given to children. The purpose of this study was to analyze the effect of individual coaching on children's health maintenance behavior during the COVID-19 pandemic. This type of research used quasy experiment with one group pre-test-posttest design. The population in this study were 143 parents of Geliting grade IV, V, VI children with a total sample size of 30 people. The technical sample in this study used Stratified Random Sampling. Measurement of health maintenance behavior using a questionnaire.Individual coaching intervention is given for 1 (one) month with several stages, namely: check in, pre visit, visit, post visit, between visits. The research is located at SD Geliting, Kewapante District, Sikka Regency. The study was conducted on 15 November -15 December 2020. Data analysis used univariate and bivariate (Wilcoxon Rank Test). The results of the Wilcoxon Rank Test analysis showed that before and after being given the individual coaching intervention, it gave a price (p-value 0.000 <0.05), this indicates that there was a significant effect caused by the individual coaching intervention. The results of this study prove that individual coaching interventions can improve health maintenance behavior in children. It is hoped that the results of this study can be used as additional interventions to improve health maintenance behavior in children.